Penerimaan Arab Saudi Terhadap Shuttle Diplomacy China dalam Normalisasi Hubungan Diplomatik Dengan Iran Tahun 2023 - Syaiful Muhammad Khadafi (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
This research aims to explain and answer the question of why Saudi Arabia accepted China's shuttle diplomacy as a medium to restore its diplomatic relations with Iran, even though previously there had been mediation efforts done by other countries. Using the 'tripartite approach' analytical framework proposed by Carlsnaes (1992), this research was discussed qualitatively deductively starting from this analytical framework. Previously there had been literature that examined China's relations, influence, and policies in the Middle East and found four main points that were the focus of this topic, namely: China's Influence in the Middle East, Economic-Political Aspects of China's Policy in the Middle East, Pragmatism in China's Policy in the Middle East, and Sino-Saudi Arabia and Sino-Iran. To fill the existing gap, this research then found that Saudi Arabia's objective conditions and institutional arrangements influenced perceptions and values which then assessed that China had a significant role without a bad historical record in the region, so Saudi Arabia with its preference chose to accept China as a mediator to improve relations with Iran.